Playing a Role as a Mediator in Resolving Child Disputes - Erwin Syahruddin; Sugeng Sugeng; Adi Nur Rohman; Diana Fitriana; Andre Cardenas; Alizah Ali (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
Sekolah Indonesia Davao (SID) in Mindanao, Philippines, was established in 1985 to provide education for Indonesian children. However, the main challenge faced is conflicts among students and between students and teachers, which are also influenced by family and social dynamics. The lack of knowledge about conflict resolution methods, such as mediation, has become a significant obstacle in creating a conducive learning environment. This activity aims to introduce mediation as a conflict resolution solution through socialization and training for students at Sekolah Indonesia Davao. The methodology used includes initial observation, interviews with teachers and students, problem mapping, the formation of a training team, and the implementation of socialization and training activities using role-playing as mediators. The results of the activity showed an increased understanding of mediation concepts and the ability to practice simple conflict resolution among students. The role-playing method proved to be effective in engaging students, although the limitation of students' proficiency in the Indonesian language was identified as one of the challenges. In conclusion, the introduction of mediation can help create more effective conflict resolution solutions in the school environment. It is recommended that similar activities be continued with a focus on improving students' Indonesian language skills and involving more stakeholders, such as parents and the local community, to broaden the program's impact. Thus, the results of this program can serve as a foundation for developing conflict resolution methods in similar schools.